Visual Splendour and Verbal Argument in Romanesque Golden Altars - Aavitsland, Kristin B. (Acta ad archaeologiam et artium historiam pertinentia, 2017)
This paper considers Latin inscriptions found on the prominent gilded metal altars from Scandinavia (c. 1130-c. 1220), aiming to discuss the possible intentions behind them and their reception by those who may have been their readers. Being highly representative of Romanesque liturgical art, the inscriptions of the Scandinavian altars are of two categories: either short, descriptive tituli identifying depicted figures or scenes or metric verses of more sophisticated, theological content. The paper discusses both types, considering their visual appearance, verbal rhetoric, and interplay with iconography. Some conclusions are drawn that may be valid for liturgical epigraphy in general. Then follows a discussion of the inscriptions of one specific altar, the spectacular frontal from Stadil Church in Denmark. Related to inscriptions on light and splendor in Rome, Saint-Denis and elsewhere, the Stadil inscription also comments on the act of reading and beholding, giving the images the pride of place above the written world. The interpretation suggested in this paper contributes to the discussion of word/image-relations in medieval religious thinking.